2023
DOI: 10.1029/2023wr035155
|View full text |Cite
|
Sign up to set email alerts
|

A Complete Water Balance of a Rain Garden

M. W. McGauley,
A. Amur,
M. Shakya
et al.

Abstract: A bioinfiltration rain garden was retrofitted from an existing traffic island at Villanova University in 2001. It has been monitored continuously since 2003 at a 5‐min timeseries resolution and with instrumentation that would enable a water balance calculation. This 20‐year data set allows for an in‐depth analysis of the hydrologic pathways and management in the rain garden. Using physical equations and modeled data (based on real‐time measurements), a balance of all influent, stored, and effluent water within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…BC, BC + PP, BC + DP, BC + PP + DP) are the most effective at preventing future CSO volume and frequency increases. Previous studies have shown that BC offer the greatest CSO reduction potential [22], given their potential to restore a degree of natural hydrology in urban catchments [66], in particular due to their ability to infiltrate run-off routed from impervious surfaces [22]. Our study confirms the superior efficacy of bioretention cells also under future climatic conditions.…”
Section: Bgi Performance Under Future Climate Conditionssupporting
confidence: 82%
“…BC, BC + PP, BC + DP, BC + PP + DP) are the most effective at preventing future CSO volume and frequency increases. Previous studies have shown that BC offer the greatest CSO reduction potential [22], given their potential to restore a degree of natural hydrology in urban catchments [66], in particular due to their ability to infiltrate run-off routed from impervious surfaces [22]. Our study confirms the superior efficacy of bioretention cells also under future climatic conditions.…”
Section: Bgi Performance Under Future Climate Conditionssupporting
confidence: 82%